Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Can someone check my work? (Algebra)?
Problem is 2[z/2 + 1] ² - 3[z/2 + 1] = -1 I am to solve for z
This is what I got:
= (2z – 1) [2(z-1)]+1
= (2z – 1) (2z – 2)
= (2z – 1) ²
3 Answers
- hayharbrLv 71 decade agoFavorite Answer
The easiest way to do this is to let x = z/2 + 1
Now you have 2x^2 - 3x = -1. Then add 1 to both sides
2x^2 - 3x + 1 = 0
Then factor by FOIL: (2x-1)(x-1) = 0
so either 2x-1 = 0 meaning x = 1/2, or x-1 = 0 meaning x=1
Then put back z/2 + 1 for x:
z/2 + 1 = 1/2 or z/2 + 1 = 1
Solve these for z.
- cidyahLv 71 decade ago
To solve for z, you must find the value of z.
2[z/2+1]^2=2[z^2/4+z+1]=z^2/2+2z+2 --- (1)
-3[z/2+1]=-3z/2-3 -----(2)
we have (1)+(2)=-1
z^2/2+2z+2-3z/2-3+1=0
z^2+4z-3z=0
z^2+z=0
z(z+1)=0
z=0 or z=-1
- 1 decade ago
0=2[z/2+1]^2-3[z/2+1]+1
let a=[z/2+1], then you'll have a quadratic equation: 0=2a^2 - 3a+1
solving for a using the quadratic formula will yield a=1 or 1/2
then, substituting it back and solving for z will give you z=0 or -1.
=)